Phát triển chương trình giáo dục nhà trường cấp trung học cơ sở: Nghiên cứu trường hợp tại tỉnh Thanh Hóa - Nguyễn, Thị Thanh; Lê, Thanh Vũ (Tạp chí Giáo dục, 2025)
Developing school education programs in secondary schools is to demonstrate the autonomy, responsibility and accountability of schools and teachers regarding the quality of education in accordance with the implementation conditions of the school and locality. The results of the case study of school education programs in secondary schools in Thanh Hoa province show that managers and teachers have paid attention to implementing the development of school education programs, but there are still limitations in some contents and steps, the reason is that managers and teachers are still limited in awareness and capacity, due to thinking according to habits and slow innovation in management thinking, therefore, based on basic contents such as: Fostering awareness and competence for managers and teachers on developing school education programs; innovating thinking in managing school education programs towards autonomy, responsibility and accountability; Strengthen inspection and supervision of teachers in developing educational plans and lesson plans, etc. in secondary schools to overcome the above limitations.